2016
DOI: 10.1126/science.aaf2807
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic stability of exhausted T cells limits durability of reinvigoration by PD-1 blockade

Abstract: Blocking Programmed Death–1 (PD-1) can reinvigorate exhausted CD8 Tcells (TEX) and improve control of chronic infections and cancer. However, whether blocking PD-1 can reprogram TEX into durable memory Tcells (TMEM) is unclear. We found that reinvigoration of TEX in mice by PD-L1 blockade caused minimal memory development. After blockade, reinvigorated TEX became reexhausted if antigen concentration remained high and failed to become TMEM upon antigen clearance. TEX acquired an epigenetic profile distinct from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
1,014
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,053 publications
(1,078 citation statements)
references
References 37 publications
63
1,014
1
Order By: Relevance
“…For instance, CD8 + T cell exhaustion is frequently observed in chronic viral infections 58 . Moreover, PD-1 blockade seems to reactivate effector T cells through the targeting of certain transcriptional factors (i.e., nuclear factor kappa-light-chainenhancer of activated B cells, interferon regulatory factors 1 and 2, orphan nuclear receptor NR4A1, and B-lymphocyte-induced maturation protein 1) that cause a reengagement of the effector mechanisms in the epigenome of exhausted T cells 59 . CTLA-4 has also been found to have a clear role in multiple chronic infections, including HBV, HCV, and HIV, and its inhibition can increase the function of pathogen-specific T cells 60,61 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…For instance, CD8 + T cell exhaustion is frequently observed in chronic viral infections 58 . Moreover, PD-1 blockade seems to reactivate effector T cells through the targeting of certain transcriptional factors (i.e., nuclear factor kappa-light-chainenhancer of activated B cells, interferon regulatory factors 1 and 2, orphan nuclear receptor NR4A1, and B-lymphocyte-induced maturation protein 1) that cause a reengagement of the effector mechanisms in the epigenome of exhausted T cells 59 . CTLA-4 has also been found to have a clear role in multiple chronic infections, including HBV, HCV, and HIV, and its inhibition can increase the function of pathogen-specific T cells 60,61 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…Blocking PD-1 can reinvigorate exhausted CD8 T cells and improve the control of cancer [35]. PD-1 pathway blockade also resulted in transcriptional rewiring and the reengagement of effector circuitry in the exhausted CD8 + T cells epigenetic landscape [36]. Here, tumour-bearing mice displayed an obvious increase of PD-1 + CD8 + T cell in tumour and spleen tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we determined if p110δ and β-catenin inhibitors could be used to enrich and expand central memory cells from fully differentiated Th17 cultures. This question is important, as TILs from cancer patients are often fully differentiated or terminally exhausted, even after ACT or PD-1 blockade therapy (31)(32)(33). As numerous studies have shown that CD62L + cells exert long-lived immunity, it is essential to find ways to preserve them in cancer immunotherapy (34)(35)(36).…”
Section: β-Catenin and Akt Rebound In Drug-treated Th17 Cells Regainimentioning
confidence: 99%